مفهوم التجريب في الرواية (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يبدو أن تحديدَ مفهوم التجريب من حيث الدلالات المفهومية والمعاني الاصطلاحية أمرٌ أساسيٌ لا محيد عنه، لكثرة تداوله وشيوعه بين الباحثين المختصين، وغير المختصين إضافة إلى ما يتضمنه هذا المفهوم من تنويع في الأساليب الفنية والأدوات الإجرائية من جهة، وما يحمله من نضج فكري وبعد إيديولوجي من جهة أخرى، لذلك يقدم هذا البحث دراسة توضيحية لمفهوم التجريب بدءاً من دلالته اللغوية والاصطلاحية، مروراً بعلاقته مع مفاهيم مقترنة به مثل مفهوم الحداثة والأصالة والتغريب، ليؤكد بذلك أن التجريب مفهوم وليس مصطلحاً، وأنه ليس تقنية بقدر ما هو تعبير عن مواقف أو رؤى فلسفية وجودية وجمالية وتاريخية تحكم مجمل العملية الإبداعية. It seems that the concept of experimentation in terms of conceptual semantics and conventional meanings is essential, inevitable, due to frequent trading and its prevalence among researchers, specialists and non-specialists in addition to what the concept of diversification in procedural techniques and tools on the one hand, and the maturity of intellectual and ideological dimension, on the other hand, this paper provides an illustrative study of the concept of experimentation from significant linguistic and idiomatic, Through its relationship with its associated concepts such as modernity, authenticity and alienation, for confirming that experimentation is not a concept, and that it is as much a reflection of attitudes or philosophical insights into Existentialism and the aesthetic and historical control the overall creative process.